Influence of Infant and Young Child Feeding Practices (IYCF) on Nutritional Status of Children Aged 6-59 Months in Moheshkhali, Cox’sbazar, Bangladesh: A Cross-Sectional Study - M Abdullah Al Masum; Taslima Ahmed; Dilshad Islam; Sadia Tuz Zohra (Health Dynamics, 2024)
Background: This study addresses the critical issue of malnutrition among under-five children in Moheshkhali, Cox's Bazar, Bangladesh. Despite the alarming rates of stunting, wasting, and underweight in this region, there is a significant lack of localized data on socioeconomic factors, IYCF practices, and overall health status. Understanding these variables is essential for developing effective interventions. Methods: The research involved a cross-sectional study design, where anthropometric measurements were conducted to assess the nutritional status of children aged 6 to 59 months. Maternal education, age, and Body Mass Index (BMI) were also evaluated to explore their impacts on child nutrition. Data were analyzed using standard statistical methods to draw correlations and identify trends. Results: The findings revealed a high prevalence of malnutrition among under-five children, with notable gender disparities in stunting and underweight. The analysis indicated a strong relationship between maternal health indicators—particularly BMI—and child nutritional outcomes. Moreover, inadequate adherence to IYCF practices was observed, with many mothers failing to implement optimal breastfeeding and complementary feeding strategies. Conclusion: The study underscores the urgent need for targeted interventions aimed at improving maternal education and IYCF practices in Moheshkhali. A multi-sectoral approach involving government and non-government organizations is essential to address the malnutrition crisis effectively. Investing in preventive measures and promoting healthy feeding practices are crucial for ensuring the well-being of both mothers and their children.